Handbook of Bereavement Research: Consequences, Coping, and Care. 2001
DOI: 10.1037/10436-027
|View full text |Cite
|
Sign up to set email alerts
|

Grief and cognitive–behavioral therapy: The reconstruction of meaning.

Abstract: Neimeyer (1998) has argued for the application of a "new wave" of grief theory, involving the need for increased attention to the cognitive processes entailed in mourning. Indeed, within the evolving, general conceptualizations of grief, there is growing understanding of the adjustment to bereavement as one of meaning reconstruction or the rebuilding of previously held assumptions (e.g., Janoff-Bulman 6r Berg, 1998). In their consideration of postmodern understandings of grief, Silverman and Klass (1996) fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 67 publications
(66 reference statements)
2
22
1
Order By: Relevance
“…Its effectiveness in treating guilt has been found for trauma survivors (Kubany & Manke, 1995). It is also helpful in reducing destructive aspects of counterfactual thinking in bereavement, which usually relate to self blame for the death (Fleming & Robinson, 2001). One study we reviewed also found supportive evidence for its effectiveness in reducing guilt among suicide survivors (De Groot et al, 2007).…”
Section: Lack Of Exploration Of Treating=reducing Guilt In Bereavementmentioning
confidence: 88%
“…Its effectiveness in treating guilt has been found for trauma survivors (Kubany & Manke, 1995). It is also helpful in reducing destructive aspects of counterfactual thinking in bereavement, which usually relate to self blame for the death (Fleming & Robinson, 2001). One study we reviewed also found supportive evidence for its effectiveness in reducing guilt among suicide survivors (De Groot et al, 2007).…”
Section: Lack Of Exploration Of Treating=reducing Guilt In Bereavementmentioning
confidence: 88%
“…Several reactions of complicated grief are described in the literature, including feelings of guilt, self-blame, anxiety and depression-related symptoms, posttraumatic stress disorders (Schut, de Keijser, van den Bout, & Dijkhuis, 1991;Zisook, Schneider, & Shuchter, 1990;Znoj & Maercker, 2004), and physical health problems (Rogers & Reich, 1988;Zisook, Shuchter, Sledge, Paulus, & Judd, 1994). Bereaved individuals often suffer from biased thinking (Fleming & Robinson, 2001), especially when analyzing the circumstances of and reasons for the death (Sherman & McConnell, 1995). In the wake of a traumatic death, many bereaved individuals experience interpersonal and intrapersonal social difficulties (Dyregrov, 2004).…”
mentioning
confidence: 99%
“…The cognitive style of each girl was assessed by how she described her thought process, feelings, and actions. Various coping strategies were introduced to include the continuation of journaling, the use of physical exercise and body movement, and cognitive restructuring by adding positive cognitions to replace or alter negative thought patterns (Fleming & Robinson, 2001). Group sessions three and four comprised this phase which parallels the group developmental stages of both power and control, and intimacy stages of group development (Garland et al, 1973) as well as those of "storming and norming" (Tuckman, 1965).…”
Section: Adolescent Grief and Loss (Agl) Group Structurementioning
confidence: 99%